Agomelatina e neuroproteção: uma nova perspectiva para tratamento da doença de Parkinson - Mesquita, Davis Nunes de (2015)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by the destruction of nigrostriatal dopaminergic neurons. There is a constant search for agents capable of inhibiting neuronal degeneration. Many studies have contributed to elucidate the pathophysiology of Parkinson's disease, and these findings provide a variety of potential targets for neuroprotective therapy. Studies have shown that agomelatine (AGO), a naphthalene analog of melatonin, has neurotrophic actions that may be correlated with possible neuroprotective effects shown in some studies with neurodegenerative diseases such as Alzheimer's disease and Amyotrophic Lateral Sclerosis (ALS). This work aims to study the behavioral and neurochemical effects of agomelatine in the animal model of Parkinson's disease induced by 6-OHDA. Male Wistar rats underwent lesion with intrastriatal 6-hydroxydopamine (6-OHDA). The animals were divided into 4 groups: sham group treated with saline; 6-OHDA control group and the groups treated with AGO (5 and 10 mg / kg). The animals were treated one hour after the lesion and daily thereafter for 21 days. At day 21, one hour after the last treatment, apomorphine-induced rotational behavior was observed, the behaviors tests rotarod and openfield were performed and in the 22th day the animals were sacrificed and the brain areas removed (striatum body-NB, hippocampus-HC and prefrontal cortex-CPF) for determination of lipid peroxidation by TBARS method. AGO reduced the number of apomorphine-induced rotations around 20% to 42% compared with the control group 6-OHDA. There was partial recovery of the motor deficit evidenced both the rota rod tests and open field test. Treatment with AGO reduced oxidative stress, with decreased levels of nitrite by 55% in the NB at the dose of 10 mg / kg compared with the 6-OHDA control group. Treatment with AGO reduced lipid peroxidation in HC by 20% and 39%, in NB at 24% and 54% at doses of 5 mg / kg and 10 mg / kg, respectively, and in the CPF there was 27% reduction in the dose of 10 mg / kg, compared to group 6-OHDA control. In addition to reducing oxidative stress and lipid peroxidation, treatment with AGO recovered glutathione levels. Agomelatine partially reversed motor deficits induced by 6-OHDA and reduced oxidative stress, showing that a potential neuroprotective agent.